Post Covid-19 Impact and Adaptations of Undergraduate Medical Education in Bangladesh - Haque, Quazi Manjurul (KYAMC Journal, 2022)
Abstract not available KYAMC Journal Vol. 13, No. 03, October 2022: 127-128